2020
DOI: 10.3389/fnint.2020.00047
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Plasma and Brain Vitamin C on Age and Gender-Related Cognitive Differences: A Mini-Review of the Literature

Abstract: Gender, Age, Vitamin C and Cognition age-associated cognitive differences, with older cohorts appearing more vulnerable to experience declines in plasma vitamin C concentrations alongside compromised vitamin C brain regulation. This review encourages future investigations to take into account both gender and age when assessing the link between plasma vitamin C concentrations and cognitive function. Further large scale investigations are required to assess whether differences in cognitive function between gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 167 publications
0
24
0
1
Order By: Relevance
“…This study demonstrated that high plasma vitamin C levels were associated with improved attention, focus, working memory, decision speed, delayed and total recall, and recognition [ 46 ]. Until recently, Travica and colleagues conducted a systemic review and highlighted the gender differences in plasma and brain vitamin C levels, which may further contribute to differences in gender-associated cognitive ability [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that high plasma vitamin C levels were associated with improved attention, focus, working memory, decision speed, delayed and total recall, and recognition [ 46 ]. Until recently, Travica and colleagues conducted a systemic review and highlighted the gender differences in plasma and brain vitamin C levels, which may further contribute to differences in gender-associated cognitive ability [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…(60) Gender differences were only considered in one trial, (47) which were averaged for the purpose of our analysis. It has recently been proposed that plasma and tissue vitamin C may be regulated diversely between genders, (96) suggesting that gender may be a variable that should be considered when assessing perioperative vitamin C concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found an effect of sex on the vitamin C distribution in the plasma and the brain. This sex difference may contribute to sex-associated cognitive ability [ 185 ]. These intriguing results require further investigation, and potential confounding variables must be identified ( Table 2 ).…”
Section: Vitamin Cmentioning
confidence: 99%